2019
DOI: 10.3390/app9020336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Operation of a Tri-Band Hydraulic Compactor on the Technical Condition of a Residential Building

Abstract: The study investigates the surface vibrations generated by a new generation, tri-band hydraulic compactor type V8 from Maschinentechnik Schrode AG (MTS), and a reversible plate compactor type DPU 6055 from Wacker Neuson in close proximity to a low-rise residential building. Compaction works were carried out in three stages, at distances: 15 m, 10 m, and 5 m from the building, and at three depths: 0.4 m, 1.2 m, and 1.8–2.0 m. The research was conducted at one measurement point, located on the outer foundation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, minimal research has explored the dynamics of the hydraulic compactor, an efficient and omni-directional reinforcement machine [16]. Although scholars obtained interesting results from the dynamic compaction impact rammer and established a dynamic model between the hydraulic-rammer and soil, the hydraulic force when the rammer comes down was not taken into account [17]. Researchers have also established a discrete element model of the hydraulic compactor reinforcing soil through numerical simulation, but this work only focuses on the rammer or the dynamic response of soil individually, rarely combining the two [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, minimal research has explored the dynamics of the hydraulic compactor, an efficient and omni-directional reinforcement machine [16]. Although scholars obtained interesting results from the dynamic compaction impact rammer and established a dynamic model between the hydraulic-rammer and soil, the hydraulic force when the rammer comes down was not taken into account [17]. Researchers have also established a discrete element model of the hydraulic compactor reinforcing soil through numerical simulation, but this work only focuses on the rammer or the dynamic response of soil individually, rarely combining the two [18].…”
Section: Introductionmentioning
confidence: 99%
“…The structure response should not be underestimated, and buildings must remain safe during dynamic excitation. Extensive comparison studies of threshold values according to different codes can be found in the literature [16][17][18][19][20]. Some general remarks on sensor arrangement are given in different codes and standards.…”
Section: Introduction: the Importance Of The Analysed Problemmentioning
confidence: 99%
“…Noise decreases not only the comfort of living, but also the comfort of work-thus negatively affecting its efficiency. In turn, intense vibrations generated by blasting (in mines, quarries, and construction sites [1,2]), ground vibrations caused by civil engineering works (passing heavy equipment [3,4], soil compaction [5][6][7][8][9], sheet pile driving and pulling out [10,11], pile driving [1,4,5,12], or traffic-induced vibrations [13][14][15][16]) can propagate over considerable distances and negatively affect not only the deterioration of living comfort and use, but also the technical condition of nearby located structures [1,4].…”
Section: Introductionmentioning
confidence: 99%